Pedagogik konfliktlarning yuzaga kelishi hamda ularni bartaraf etish usullari - Nurmatova Mohlaroyim Zarip qizi, Rayimova Robiyaxon Oʻrol qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In their activities, teachers face problems related to the discipline of the students, that is, the negative attitude of the students towards their education and learning. They make certain demands on the students and they think that the students will follow these demands without question. The relationship between a student and a teacher can be compared to a conflict on the street, because the attitude of the student to the teacher is manifested in the form of conflict and problematic behavior. In order to have a constructive influence on those who do not follow discipline, it is necessary to determine what are the real motives of this behavior and, based on this, to choose the methods of finding a solution to the problem. This approach builds mutual respect between the teacher and the student.